Pelaksanaan sistem pembangunan tanah bersepakat (PTB) dalam menyusun semula tanah : Kajian Kes : Projek PTB Kampung Pulau Meranti Daerah Sepang,Selangor - Baharom, Mohd. Shukri (2010)
The government of Malaysia has introduced a new method of land development namely Sistem Pembangunan Tanah Bersepakat (PTB). This method is a very suitable way to develop remote areas that are far from such a more sound enviroment. This system of PTB is also a new method of land development especially in the rearrangement of land in this country where some of the unsystematically developed land and those undeveloping have been rearranged with the adequate supplement of basic and public facilities through the collaboration and agreement from the land’s owner. As a return of some contributed lands, the owners will be received compensation in the form of properties and other forms of incentives. Another lands will be formed as financial land and will be sell in the market in order to support some cost of project development. This financial land can be in the form of empty lots or treasuries that has been developed. From this conducted research, it can be concluded that, in overall, this system of PTB is such a comprehensive system of land development, but, this system needs to be supported by a specific law or act. This is because, this system is very hard to attain an agreement from all of the land owners. Therefore, this research suggests some actions to improve the current law of this PTB’s system. The research found some problems in PTB’s system are because of elements of PTB are not being allocated in any laws in this country. Furthermore, to initiate a project in PTB which includes a research and construction, one round-financial fund (or one cycle-financial fund) should be formed by the federal goverment to promote the smoothness of this project’s development. This fund will be act as a resource to provide an interest-free loan to PTB’s projects while waiting for the influx of project’s financial resource via the financial land’s sale.